2017
DOI: 10.1007/s10815-017-1014-3
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mutation carriers have a lower number of mature oocytes after ovarian stimulation for IVF/PGD

Abstract: PurposeThe aim of this study was to determine whether BRCA1/2 mutation carriers produce fewer mature oocytes after ovarian stimulation for in vitro fertilization (IVF) with preimplantation genetic diagnosis (PGD), in comparison to a PGD control group.MethodsA retrospective, international, multicenter cohort study was performed on data of first PGD cycles performed between January 2006 and September 2015. Data were extracted from medical files. The study was performed in one PGD center and three affiliated IVF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…It would be of particular interest to assess which is the relevance of these oncologic events as confounding factors in BRCA1/2 women reduced fertility. [13,[15][16][17] The previous six studies related to this topic, addressing ovarian stimulation in BRCA 1/2 subjects, did not analyze in detail the potential role of oncologic history itself, independent of BRCA mutations, as fertility performance determinant [16,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It would be of particular interest to assess which is the relevance of these oncologic events as confounding factors in BRCA1/2 women reduced fertility. [13,[15][16][17] The previous six studies related to this topic, addressing ovarian stimulation in BRCA 1/2 subjects, did not analyze in detail the potential role of oncologic history itself, independent of BRCA mutations, as fertility performance determinant [16,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The number of oocytes produced by women with BRCA mutation is lower than without BRCA1 mutation. [160] DNA damage and repair capacity of aged and young buffalo ovaries.…”
Section: Retrospective Cohort Study Brca1 and Brca2mentioning
confidence: 99%
“…It has been hypothesized that BRCA mutation carriers, especially BRCA1 mutation carriers, are correlated with decreased ovarian reserve, increased fertilityrelated problems and primary ovarian insufficiency. These can all lead to infertility and early menopause [21][22][23][24]. Cumulative evidence has shown that BRCA mutation negatively affect carriers' ovarian reserve and accelerate ovarian aging, impacting reproductive outcomes both quantitatively and qualitatively.…”
Section: Main Textmentioning
confidence: 99%
“…Based on convincing evidence from in vivo results and prospective studies, women with BRCA1 mutation show accelerated ovarian aging due to function of the intact gene decline. This occurs at an earlier age compared to those with BRCA2 mutation [21,25]. While BRCA1 and BRCA2 are crucial members of the ataxia-telengiectasia mutated (ATM) -mediated double strand break (DSB) repair family of genes, impaired ATM mediated DSB repair act as a cause of aging in human oocytes [26].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation